PT. Alfa Mulia Global Advertising Pattern in Finding An International Scale Buyer - Bobby Martin Muhammad; Syukur Kholil (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
The purpose of this research is to determine the advertising pattern used by PT. Alfa Mulia Global when looking for foreign buyers or buyers on a global scale. Advertising theories serve as a theoretical foundation for analyzing the problems in the research. The descriptive qualitative approach is used in this study. In the study, informants included the owner of PT. Alfa Mulia Global, the company manager, public relations, and business development. The researcher employs the activities of interviewing, observing, and documenting all of the researcher's informants. The researcher conducts a phenomenological study to determine the meaning of the phenomenon of advertising activities that occur in the company. The researcher uses descriptive data analysis to summarize all of the data generated from interviews using the data validity technique of triangulation, which is to check the data obtained from all informants. There are three types of triangulation or checking, namely source triangulation, data collection technique triangulation, and time triangulation. According to the findings of this study, the Company plans all aspects of its marketing and advertising strategies systematically and on a regular basis.